Efecto neuroprotector de hidroxitirosol en un modelo experimental de diabetes - Romero Gómez, Lidia (Universidad de Málaga, Servicio de Publicaciones y Divulgación Científica, 2014)
The salutary effects of olive oil on many cardiovascular risk factors have beendocumented scientifically as beneficial for the lipid and thrombotic profile, insulin-mediated glucose metabolism, blood pressure, homeostasis, endothelial function, inflammation and oxidative stress. Although different components in virgin olive oil (VOO) such as oleic acid can show properties that benefit health, there is a general consensus that polyphenols are one of the components responsible for these benefits. The polyphenol present at highest concentrations in VOO is hydroxytyrosol (3,4- dihydroxyphenylethanol) (HT). The aim of the present study was to evaluate the neuroprotective effects of hydroxytyrosol in streptozotocin-diabetic rats. Material and Methods. The study was carried out on two-month evolution diabetic rats induced with streptozotocine. Seven groups of rats (N = 10 rats per group) were constituted: non diabetic rats (NDR), diabetic rats without treatment with HT (DR) and diabetic rats treated from the first day of diabetes (blood glucose>11.1 mmol/L) with HT (0.5, 1, 2.5, 5 y 10 mg/kg/day, respectively). HT was administered orally once a day. We tested all concentration of the compound in an experimental model of hypoxia-reoxygenation in rat brain slices (De la Cruz et al., 2004). At the end of the experimental follow up, cell death was measured as an increase in LDH efflux. Results. We observed an increase in cell death, trough the LDH value in the group of diabetic rats (3.519±0.364) from the group respect to non-diabetic rats (2.347±0.113)
Keywords: Diabetes - Aspectos nutricionales -Tesis doctorales; Neuroprotección; Diabetes Mellitus; Aceite de oliva; Hidroxitirisol